Análise dos elementos da estratégia de marketing e dos aspectos de relacionamento no canal entre atacado distribuidor, indústria alimentícia e pequeno varejo - Souza, Thiago Alves de (2016)
Due to the complexity of markets and intense competition organizations are looking for new ways to generate sustainable competitive advantage, that it is the competitive advantage that can not be copied in the short term by competitors. In this sense, the distribution channels emerge, which are the set of interdependent organizations involved in the process of making a product or service available for use or consumption. Integrating the distribution channel as intermediaries are wholesalers and retailers, who act as an important link between the industry and the end consumer. In general, these organizations carry out a number of elements of the marketing strategy in the distribution channel and so develop and maintain long-term relationships with partners and other channel members. The objective of this research is to identify how the elements of the marketing strategy influence on the aspects of the relationship. This study has as its core the wholesale distributor perspective, but also identifies the views of small food and retail industry. This research has qualitative and exploratory nature character, using as main methods the case study and the technique of critical incident. As a data collection instrument, we opted for the construction of semistructured in order to support the conduct of interviews. nine interviews were conducted, two in the distributor wholesaler four in food industries and three small retailers. For data analysis, we used the technical characteristics of the critical incident, content analysis and triangulation. The survey results identified the elements of the marketing strategy and relationship issues primarily from the perspective of distributor wholesaler. It has been found empirically that targeting influences the trust; the element influencing product partnerships and satisfaction; price element affects power / dependence, conflict, cooperation and satisfaction; element of marketing communication relates to investment, exchange of information and commitment; element distribution influences the conflict, among other relations. Ultimately, this study presents an analysis of the gaps / shortcomings as they relate to the elements of the marketing strategy developed by the wholesale distributor or the aspects of the relationship with food and small retail industry. Finally, we present the implications both managerial and theoretical, limitations and future research suggestions.